Potential of newly isolated strain Pseudomonas aeruginosa MC-1/23 for the bioremediation of soil contaminated with selected non-steroidal anti-inflammatory drugs - Klim, Magdalena; Żmijowska, Agnieszka; Cycoń, Mariusz (Frontiers in Microbiology, 2025)
The widespread usage of non-steroidal anti-inflammatory drugs (NSAIDs) has resulted in their significant accumulation in the environment, necessitating the development of effective methods for their removal. This study primarily isolated a bacterial strain capable of degrading specific NSAIDs and evaluated its potential for eliminating these drugs from contaminated soil through bioaugmentation. The objectives were achieved by assessing the degradation rates of ibuprofen (IBF), diclofenac (DCF), and naproxen (NPX) in liquid media and soil samples inoculated with a newly identified strain, Pseudomonas aeruginosa MC-1/23. In addition, the effect of natural soil microflora and abiotic conditions on the breakdown of the tested NSAIDs was examined. The findings revealed that strain MC-1/23 could metabolize these compounds in a mineral salt medium, utilizing them as carbon and energy sources, suggesting metabolic degradation. When nonsterile soil was augmented with the P. aeruginosa MC-1/23 strain, the degradation rates of the drugs significantly improved, as evidenced by reductions in t1/2 values by 5.3-, 1.4-, and 5.8-fold for IBF, DCF, and NPX, respectively, compared with soil containing only natural microflora. These results confirm that the introduced strain enhances the catabolic potential of existing microflora. Thus, the strain’s degradation and bioremediation capabilities offer valuable applications for remediating NSAID-contaminated soils.